Hubungan Pengetahuan tentang Covid-19 terhadap Kecemasan Ibu Hamil Trimester III - Verawati Verawati; Arum Meirany; Alfiah Rahmawaty (Politeknik Kesehatan Tanjung Karang, 2021)
Pregnant women will experience physiological changes during pregnancy that can make these pregnant women more susceptible to infections, including Covid-19 infection. In Indonesia, there were 74,018 positive cases of Covid-19 until July 11, 2020, with a total of 34,719 recovered cases and 3,535 deaths. As a result of this situation, leads to increased stress and anxiety. One of the factors that influence anxiety is knowledge. This study aimed to know relationship between knowledge about covid-19 and anxiety of third trimester pregnant women at Tlogosari Wetan Community Health Center. The research design used was observational with a cross-sectional approach. The sample of this study consisted of 40 respondents which were conducted on 27 October-10 November 2020. The instruments used in this study were a knowledge questionnaire about Covid-19 and an anxiety level questionnaire. The analysis used is the chi-square test. The results 18 pregnant women with sufficient knowledge, namely 7 pregnant women did not experience anxiety, and 11 pregnant women experienced mild anxiety. 22 pregnant women who have less knowledge, namely 12 pregnant women do not experience anxiety, and 10 pregnant women experience moderate anxiety. There is no significant relationship between knowledge of Covid-19 and anxiety of third-trimester pregnant women at Tlogosari Wetan Community Health Center (ρ-value=0,324).